A facile synthesis of CuFe2O4/Cu9S8/PPy ternary nanotubes as peroxidase mimics for the sensitive colorimetric detection of H2O2 and dopamine. Issue 34 (16th August 2017) - Yang, Zezhou; Ma, Fuqiu; Zhu, Yun; Chen, Sihui; Wang, Ce; Lu, Xiaofeng
Abstract : CuFe2 O4 /Cu9 S8 /PPy ternary nanotubes as robust peroxidase-like mimics for the sensitive detection of dopamine have been developed. Abstract : Synergistic effects play an important role in improving the catalytic activity for enzyme-like reactions. Compared to individual nanomaterials, a system consisting of multiple components usually exhibits enhanced catalytic activity as an enzyme mimic. Herein we describe the synthesis of CuFe2 O4 /Cu9 S8 /polypyrrole (PPy) ternary nanotubes as an efficient peroxidase mimic via a three-step approach involving an electrospinning process, annealing treatment and hydrothermal reaction. The remarkably enhanced catalytic activity of CuFe2 O4 /Cu9 S8 /PPy ternary nanotubes as peroxidase mimics over individual CuFe2 O4 nanofibers, CuFe2 O4 /CuO composite nanofibers, CuFe2 O4 /CuS composite nanofibers, and PPy materials has been achieved, demonstrating the presence of a synergistic effect among the components. The steady-state kinetic experiment suggests a good catalytic efficiency of the CuFe2 O4 /Cu9 S8 /PPy ternary nanotubes. On the basis of high catalytic activity, a colorimetric platform for the sensitive detection of H2 O2 and dopamine has been developed. This work not only offers a simple approach for the fabrication of a high performance peroxidase-like nanocatalyst, but also provides its promising potential applications in biosensors, medical diagnosis, and environmental monitoring.